Penerapan Sistem Informasi Sumber Daya Manusia Pada Program E-Kinerja Di Badan Kepegawaian, Pendidikan Dan Pelatihan (BKPP) Kabupaten Kuantan Singingi - Ryndian Gusty; Harapan Tua Ricky F S; Adianto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
Covid-19 Pandemic does not mean the obligation to remain productive. Performance assessments continue to run and job demands are also not diminished.Everyone should utilize the best possible time including the free time they have to follow a wide range of activities organized online.Research respondents spread across 24 provinces in Indonesia. Data is obtained by a descriptive quantitiative approach using data collection methods via closed poll and distributed through Google online form on June 19 to June 30, 2020.From the process of spreading Google form links on various social media such as WhatsApp, Instagram, Telegram, and Facebook, the authors get respondents as many as 218 people.The results showed that 63.3 percent of male sex respondents. The level of education of respondents was at the undergraduate and master's degree with the same percentage of 43.6 percent.The respondent's educational background is an educator of both teachers and lecturers with a percentage of 77.1percent.The reason for following the webinar was to fit the job with a 61.5percent response percentage.While the average respondent is willing to contribute or give a fee as long as it gets a certificate with a percentage of 52.3percent.Media access is the most dominant iformation is WhatsApp with a percentage of 74.3percent.